(untitled) (Journal of the College of Basic Education, 2022)
The study in title ( fantasy in nazeef al-hajar novel by Ibraheem al- kaony) focuseson the most important modren issue of Arabic novel as fantasy literature issue or queerness and how the writer can employ this technique of writiny in literary works-the novel in its generic sence reflects social , humanstic and psycholojical syatus in life . The written tries to create to us in his turn a new world which differs from our real world and this is exactly the role of the literature in creuting a simulation of reality bit not the reahty it self . The writer ( Ibraheem al-kaony ) tries in this novel (nazeef al-hajar) in his other novels to create to us a fantasy and strange world by employing the characters , events and places in fantasy concept , so we see the animal " Al-wedan" and "Aswoof " character and the desert and its relation with fairyland , superstation and fortuneteller speech , all these elements are inserted under the fram of fantasy literature . The writer presents "narrative literature " by inserting fantasy events inside the real world in that way the natural text is transferred to fantasy text .